Memory advantage for produced words and familiar native accents. Issue 5 (18th August 2018) - Grohe, Ann-Kathrin; Weber, Andrea
ABSTRACT: Our memory is better for words that we have read aloud than for words that we have read silently or have listened to. The present study tested this memory advantage for words with native accent markers that participants were either highly familiar or less familiar. As in previous studies, produced words were subsequently remembered better than listened-to words. In contrast to previous studies that involved a comparison of global foreign accents with standard native accents, in the present study words with highly familiar accent markers were remembered better than words with less familiar accent markers (Experiment 1). The familiar accent advantage was also found when participants could not hear their own productions during the training phase (Experiment 2). When tested with a week delay, produced words were still remembered better than listened-to words, but the advantage for words with familiar accent markers was no longer found (Experiment 3).